Determinación de las constantes fisiológicas en caninos con relación a la situación geográfica - Chafla Valverde., Jeniffer Patricia (2019)
The objective of this research is to address the determination of physiological constants in canines in relation to the geographical situation of the cantons: Guaranda (2800msnm), San Miguel (2480msnm) and Balsapamba parish (720msnm) of the Bolívar province during the period 2018-2019 in order to identify the physiological values of canines through the hematocrit, evaluate the physiological constants according to their habitat and establish the physiological constants according to the geographical situation being: Heart rate, Pulse, mucous respiratory rate, filling time capillary, temperature and hematocrit. Using a descriptive, investigative and experimental methodology. It is a field investigation since the data were taken in a population of one hundred and eighty canines distributed sixty dogs in each of the locations under study, for this purpose clinical records, general clinical examination and hematocrit examination were used. The results indicated that the geographical situation influences the physiological constants, due to the height and the greater the height there is an increase in hematocrit values, the increases in heartbeat increases per minute in the areas of Guaranda and San Miguel instead lower height there was no increase in the parameters of the constants favoring the geographical situation of the Balsapamba sector Concluding that the geographical situation affects the physiological constants with the results of the values, samples and analysis of the population studied. In addition, applying the appropriate safety regulations and precautions in making them to avoid alterations in the results.